Academic Leadership of School Heads and Teachers’ Professional Conduct - Virtudazo, Alicia (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Fundamentally, academic leadership of school heads is a measure expected to improve the professional conduct of teachers. In this study, the researcher selected the 205 secondary school teachers in District 1 in Davao City as the respondents of the study. Stratified random sampling technique was utilized in the selection of the respondents. Non-experimental quantitative research design using descriptive-correlational method was employed. The data collected were subjected on the following statistical tools: Mean, Pearson Moment Product Correlation and multiple linear regression analysis. Findings revealed that academic leadership of school heads and professional conduct of teachers in District 1 in Davao City were described as moderately extensive. Further, correlation analysis demonstrated that there is a significant relationship between academic leadership of school heads and professional conduct of teachers in Tugbok District 1 in Davao City. Evidently, regression analysis proved that academic leadership of school heads in terms of efficient planning and systematic inquiry were significant predictors of professional conduct of teachers in District 1 in Davao City. The study, therefore, conducted for further utilization of findings through publication in reputable research journal.